Cytokines induced memory-like NK cells engineered to express CD19 CAR exhibit enhanced responses against B cell malignancies - He, Bailin; Mai, Qiusui; Pang, Yunyi; Deng, Shikai; He, Yi; Xue, Rongtao; Xu, Na; Zhou, Hongsheng; Liu, Xiaoli; Xuan, Li; Li, Chengyao; Liu, Qifa (Frontiers in Immunology, 2023)
CD19 chimeric antigen receptor (CAR) engineered NK cells have been used for treating patients with relapsed and/or refractory B cell malignancies and show encouraging outcomes and safety profile. However, the poor persistence of NK cells remains a major challenge for CAR NK cell therapy. Memory-like NK cells (MLNK) induced by IL-12, IL-15, and IL-18 have shown enhanced and prolonged responses to tumor re-stimulation, making them an attractive candidate for adoptive cellular immunotherapy. Here, we show efficient and stable gene delivery of CD19 CAR to memory-like NK cells using retroviral vectors with transduction efficiency comparable to those achieved with conventional NK cells. Analysis of surface molecules revealed a distinct phenotypic profile in CAR engineered memory-like NK cells (CAR MLNK), as evidenced by increased expression of CD94 and downregulation of NKp30 as well as KIR2DL1. Compared to conventional CAR NK cells, CAR MLNK cells exhibited significantly increased IFN-γ production and degranulation in response to CD19+ target cells, resulting in enhanced cytotoxic activity against CD19+ leukemia cells and lymphoma cells. Furthermore, memory properties induced by IL-12/-15/-18 improved the in vivo persistence of CAR MLNK cells and significantly suppressed tumor growth in a exnograft mouse model of lymphoma, leading to prolonged survival of CD19+ tumor-bearing mouse. Altogether, our data indicate that CD19 CAR engineered memory-like NK cells exhibited superior persistence and antitumor activity against CD19+ tumors, which might be an attractive approach for treating patient with relapse or refractory B cell malignancies.